Anti-kripkean intuitions: conceptualism versus essentialism - Sepetyi, D. P.; Сепетий, Дмитро Петрович (My University, 2022)
The article discusses Saul Kripke’s criticisms of the account of the reference of general names he called “descriptivism” and the considerations he advanced in favour of his own essentialist causal-histori cal account of the reference of natural kind terms. The alternative of conceptualism versus essentialism about the reference of general terms is explained in details. The case is made that most of the intuitions on which Kripke based his arguments are highly controversial, and the main examples he used to explain and support his views (such as examples of whales and fish, water and H20, gold, tigers, and unicorns) do not constitute a clear case for the preference of essentialism over conceptualism. Mo re over, these examples can be modified in such ways that in the perspective of these modifications, Kripke’s essentialist construal turns out to be far-fetched and implausible, whereas a form of conceptualism (the cluster theory of reference) is tenable.
https://orcid.org/0000-0003-2110-3044
Keywords: general name; natural kind; conceptualism; descriptivism; the cluster theory; essentialism; reference